Nursing staffs' attentiveness to older adults falling in residential care – an interview study. Issue 9 (24th March 2016) - Clancy, Anne; Mahler, Marianne
Abstract : Aims and objectives: The focus of this study is to explore how nursing staff experience safety promotion and fall prevention in residential care settings for older adults. The article calls for attentiveness to fall prevention within a broader lifeworld context of well‐being and health promotion. Background: There is limited research on fall prevention and safety promotion where the lifeworld and well‐being provide a direction for care. Design: This interview study has a hermeneutic phenomenological design. Methods: Fourteen interviews with nursing staff were carried out. The ethics of care and vulnerability within a lifeworld approach provide the theoretical framework and guide the interpretive process. Results: The findings can indicate that there is a generalised understanding of the needs of older persons in residential care. The focus of the staff was more on protection and prevention than safety promotion and well‐being. Conclusion: Risk prevention is not enough. The residents need protection against falls but they also need to be protected from situations that can be detrimental to their well‐being and compromise their dignity. Acknowledging the complexities of safety promotion amongst older persons living in assisted care settings can prevent fall accidents and ensure attentiveness to a more fundamental sense of security that can promote the older person's well‐being and health. Relevance to clinical practice: This study is relevant to clinical nursing practice as it shows that risk management in fall prevention is not enough. The findings show the need for educated nursing home staff that can incorporate contemplative and scientific knowledge into injury prevention practice.